Peri-implant therapy for the dental hygienist clinical guide to maintenance and disease complications - Wingrove, Susan S. (Ames, Iowa : Wiley Blackwell, 2013)
"Peri-Implant Therapy for the Dental Hygienist is a comprehensive guide for implant history, prosthetic designs, and patient selection including oral systemic health and risk assessment. The text also discusses pre-surgical procedures, communicating with patients about implant dentistry, in-office maintenance protocols, plus new innovative home-care options to ensure success of the implant and overall health of the patient. An essential tool for dental hygienists to prepare to take on this very important challenge in the profession, Peri-Implant Therapy for the Dental Hygienist is a valuable resource for the entire dental team"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Dental implants; Dental hygienists; Dental implants -- Side effects; Electronic books